Control instability applied to a micro electro mechanical actuator system (mems) - De Conde, Kevin Eduardo [UNESP]; Chavarette, Fábio Roberto [UNESP] (Trans Tech Publications, 2014)
MicroElectroMechanical Systems (MEMS) are devices what have been considered the technology of the future, being used in too many areas. MEMS are a combination of microstructures, micro sensors and micro actuators. The purpose of this work is to reduce the chaotic movement of the micro-actuator electrostatic to a small periodic orbit using the linear optimal control technique. The simulation results show that this technical is very effective.
Keywords: Actuator; Chaos; Linear optimal control; MicroElectroMechanical System